Scalable Fabrication of Methylammonium-Free Wide-Bandgap Perovskite Solar Cells by Blade Coating in Ambient Air - Jianbo Liu; Meng Zhang; Xiaoran Sun; Linhu Xiang; Xiangyu Yang; Xin Hu; Zhicheng Wang; Tian Hou; Jinzhao Qin; Yuelong Huang; Mojtaba Abdi-Jalebi; Xiaojing Hao (Nano-Micro Letters)
Highlights RbI is the most effective in mitigate PbI2 precipitation caused by Pb(SCN)2 while maintaining large grains. Rb is kept at the grain boundaries during crystallization and Ostwald ripening, contributes to a slow growth of the grains. Wide-bandgap perovskite solar cells with blade-coated perovskite in air achieved a certified power conversion efficiency of 23%, among the highest values reported.